The Effect of Product Innovation, Brand Image, and Utilization of E-Commerce on Consumer Purchase Decisions: Pengaruh Inovasi Produk, Brand Image, dan Pemanfaatan E-Commerce Terhadap Keputusan Pembelian Konsumen - Bahalwan, Faiz; Indayani, Lilik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine that product innovation, brand image, and e-commerce have a simultaneous effect on consumer purchasing decisions. In mid-March 2020 the whole world was struck by a calamity. This disaster is known as the Covid-19 pandemic. All existing sectors have had a negative impact due to the Covid-19 pandemic, one of which is the economy. Where MSME traders who sell online are also affected by the Covid-19 pandemic. The income they receive is drastically reduced, eventually resulting in bad effects for the sustainability of their business. The problem in this study is that there are differences between previous research and the research that will be carried out. In this study using quantitative methods. According to Zechmester (2000) quantitative research can be regarded as a method that describes a study whose assessment focuses on the relationship between variables that arise naturally. Meanwhile, the data analysis technique used in this research is data quality test, classical assumption test, and multiple linear regression analysis. The results show that Product Innovation has a significant effect on consumer purchasing decisions. Brand Image has no effect on consumer purchasing decisions. E-Commerce has an effect on consumer purchasing decisions.